Phylogenetic Characterization of Rabies Virus Field Isolates Collected from Animals in European Russian Regions in 2009–2022 - Sergei A. Chupin; Alexandr V. Sprygin; Nikolay G. Zinyakov; Nelly A. Guseva; Sergey V. Shcherbinin; Fedor I. Korennoy; Renat V. Adelshin; Ali Mazloum; Andrey Y. Sukharkov; Victoria V. Nevzorova (Microorganisms, 2023)
Rabies is a fatal disease of mammals that poses a high zoonotic risk to humans as well. The distribution of rabies is mainly driven by host animal migration and human-mediated dispersion. To contribute to the global understanding of the rabies virus (RABV) molecular epidemiology, 94 RABV field isolates collected from animals in 13 European Russian regions were phylogenetically characterized using the nearly full-size N gene nucleotide sequences. According to phylogenetic inferences, all isolates belonged to one of the two established phylogenetic groups, either group C (n = 54) or group D (n = 40), which are part of the clade Cosmopolitan of RABVs. Some representatives of group C collected from regions located far apart from each other had a remarkably high level of nucleotide identity. The possibility of the contribution of local bat species to the distribution of RABVs was discussed. Interestingly, over the years, the fraction of group D isolates has been constantly decreasing compared with that of group C isolates. The phylogenetic insights generated herein might have an important contribution to the control and surveillance of animal rabies epidemiology in the region.